ON CONTRA Λ s I -CONTINUOUS FUNCTIONS AND THEIR APPLICATIONS (2021)
In this work, we introduce and study the classes of contra Λ s I -continuous, contra quasi-Λ s I -continuous and contra Λ s I -irresolute functions in a topological space endowed with an ideal. We investigate the relationships among these functions and their respective characterizations. Also, we analyze the behavior of certain topological notions under direct and inverse images of these new classes of functions.